Prediction of the toughness of date palm fruit - Ahmed M. Hassan; Mohamed M. Ibrahim; Mohamed Ghonimy; Maher Fathy (Scientific Reports)
Abstract This study aimed to predict the toughness of date palm fruit (Barhi, Saqie, and Khodry varieties) at different ripening stages (Khalal, Rutab, and Tamar) using Hertz Theory by evaluating the physical and mechanical characteristics of the fruits. Physical measurements revealed that high moisture content in the Khalal stage led to larger dimensions and mass across all varieties, with Barhi dates showing a moisture content of 63.31%, which decreased to 32.60% at Rutab as the fruit dehydrated. This moisture reduction also impacted other characteristics, such as bulk density, volume, and flesh thickness, resulting in a concentrated, denser structure in the Tamar stage. Mechanical analysis demonstrated significant softening in all varieties as they transitioned from Khalal to Rutab stages, with Barhi dates’ modulus of elasticity dropping from 548.83 to 16.72 kPa. Similarly, bioyield and rupture stress decreased, highlighting the influence of moisture loss on textural characteristics. Saqie and Khodry varieties followed similar trends, with initial softening from Khalal to Rutab, and a slight firmness increase at Tamar due to dehydration. The force-deformation curves and toughness measurements confirmed these findings, showing significant reductions in toughness from Khalal to Rutab, with a slight increase in Tamar. These results underscore the pronounced textural and structural changes as dates ripen, influencing their suitability for different applications. Also, the measured toughness (τm) closely aligned with predicted toughness (τp), with significant textural differences observed across varieties and ripening stages. For all varieties, the τp is approximately 0.00–9.24% lower than the τm. Finally, the derived equation can be used with enough confidence to theoretically predict the toughness of date palm fruit.